Effect of 3D printer, implant analog system, and implant angulation on the accuracy of analog position in implant casts - Rutk?nas, Vygandas; Jegelevi?ius, Darius; Gedrimien?, Agn?; Revilla León, Marta; Pletkus, Justinas; Akulauskas, Mykolas; Eyüboğlu, Tan Fırat; Özcan, Mutlu; Auškalnis, Liudas (My University, 2024)
Objectives: To evaluate the accumulative effect of 3D printer, implant analog systems, and implant angulation on the accuracy of analog position in implant casts. Methods: A reference cast, presenting a case of a three-unit implant-supported prosthesis, was scanned with a coordinate measurement machine, producing the first reference data set (CMM, n = 1). The second reference data set (n = 10) was prepared using an intraoral scanner (IOS) (Trios4). Test quadrant casts were produced using three DLP type 3D printers, Max (MAX UV385), Pro (PRO 4K65 UV), and Nex (NextDent 5100), and three implant analog systems, El (Elos), Nt (Nt-trading), and St (Straumann) (n = 90). Stone casts were also produced via analog impressions (Stone, n = 10). After digitization, the accuracy of 3D distance, local angulation (angle between implants) and global angulation (angle between the implant center axis and an axis perpendicular to the global plane) was evaluated by comparing the reference (CMM, IOS), test (3D print), and control (Stone) groups using metrology software. Data were statistically analyzed using three-way ANOVA and Tukey`s tests (?=0.05). Results: IOS was truer in 3D implant distance and more precise in capturing local angulation than Stone (p ? 0.05). Other measurements were similar between both groups (p > 0.05). The amount of error introduced in the workflow by IOS and 3D printing was mostly similar (p > 0.05). 3D printed casts had similar or even higher accuracy than Stone group (p > 0.05). In most cases, higher trueness was achieved when using PRO 4K65 UV 3D printer and Elos implant analog system (p ? 0.05). Conclusion: 3D printer, implant analog system, and implant angulation have a significant effect on the accuracy of analog position in implant casts. Limited-span implant-supported cases could be reproduced digitally with similar accuracy as conventional methods. Clinical significance: A fully digital workflow with a carefully selected 3D printer and implant analog system can increase the accuracy of digitally produced implant casts with comparable accuracy to conventional workflow.
Keywords: 3D Printing; Accuracy; Dental Materials; Digital Dentistry; Implant Analog; Intraoral Scanner; Precision; Prosthodontics; Trueness